Dividends, earnings and stock prices: a case of Nepalese insurance companies - Lamichhane, Sabina; Rai, Sarina (Nepalese Journal of Insurance and Social Security, 2021)
The study examines the relationship among dividends, earnings and stock prices of Nepalese insurance companies. Market price per share and stock return are the dependent variables. The independent variables are earning per share, dividend per share, dividend payout ratio, PE ratio, return on assets and return on equity. This study is based on secondary data of 15 insurance companies with 105 observations for the period of 2011/12 to 2017/18. The data were collected from the annual reports of the selected insurance companies. The regression models are estimated to test the significance and importance of dividends, earnings and stock prices in Nepalese insurance companies. The result shows that earning per share has a positive impact on market price per share and stock returns. It reveals that increase in earnings per share leads to increase in market price per share and stock returns. Similarly, PE ratio has a positive impact on market price per share and stock returns. It shows that increase in PE ratio leads to increase in market price per share and stock returns. Likewise, return on equity has a positive impact on market price per share and stock returns. Similarly, higher the return on equity, higher would be the market price per share and stock returns. The result also shows that dividend per share has a positive impact on market price per share. It indicates that increase in dividend per share leads to increase in market price per share. Similarly, dividend payout ratio has a positive impact on market price per share. It shows that increase in dividend payout ratio leads to increase in market price per share. Likewise, return on assets has a positive impact on stock return. It shows that higher the return on assets, higher would be the stock returns. However, dividend payout ratio has negative impact on stock return which reveals that higher the dividend payout ratio lower would be the stock return. Likewise, dividend per share has a negative impact on stock return which reveals that higher the dividend per share lower would be the stock return. Similarly, return on assets has negative impact on market price per share which reveals that higher the return on assets lower would be the market price per share.